2016
DOI: 10.5966/sctm.2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

β-Elemene Selectively Inhibits the Proliferation of Glioma Stem-Like Cells Through the Downregulation of Notch1

Abstract: Glioma is the most frequent primary central nervous system tumor. Although the current first‐line medicine, temozolomide (TMZ), promotes patient survival, drug resistance develops easily. Thus, it is important to investigate novel therapeutic reagents to solidify the treatment effect. β‐Elemene (bELE) is a compound from a Chinese herb whose anticancer effect has been shown in various types of cancer. However, its role in the inhibition of glioma stem‐like cells (GSLCs) has not yet been reported. We studied bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Western blot analysis was performed using a standard protocol 36 . Briefly, equal amounts of protein (30 μg) were separated via SDS-PAGE and electro-transferred onto polyvinylidene difluoride membranes (EMD Millipore).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Western blot analysis was performed using a standard protocol 36 . Briefly, equal amounts of protein (30 μg) were separated via SDS-PAGE and electro-transferred onto polyvinylidene difluoride membranes (EMD Millipore).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The in vivo animal work followed previously published protocol [18]. Four-week-old female BALB/C nude mice (Charles River Laboratories, Beijing, China) were raised in Sun Yat-sen University Cancer Center (SYS-UCC) animal facilities.…”
Section: Xenograft Transplantation In Vivomentioning
confidence: 99%
“…Research has found that β-elemene has direct antitumor effects, and its antitumor mechanisms include inducing apoptosis [10], arresting the cell cycle [11], inhibiting angiogenesis and cell migration [12], enhancing the immunogenicity of tumor cells [13], promoting erythrocyte immune function, and inhibiting cancer stem cell-like effects [14]. β-Elemene not only has direct antitumor effects but also reverses multidrug resistance by reducing mitochondrial membrane potential, activating the intracellular redox system, and inducing apoptosis of tumor cells [10,15].…”
Section: Introductionmentioning
confidence: 99%